Effects of corn particle size, complete diet grinding, and diet form on 24- to 50-lb nursery pig growth performance - De Jong, Jon A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Hastad, C. W.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 996 pigs (PIC TR4; initially 24.5 lb BW and 40 d of age) were used in a 21-d study to determine the effects of corn particle size, complete diet grinding, and diet form on nursery pig growth performance and caloric efficiency. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 6 dietary treatments with 6 replications per treatment and 28 pigs per pen. The same corn-soybean meal–based diet containing 30% corn dried distillers grains with solubles (DDGS) and 10% wheat middlings (midds) was used for all treatments. The 6 treatments were: (1) roller mill– ground corn (737 µ) fed in meal form; (2) treatment 1 fed in pellet form; (3) hammer mill–ground corn (324 µ) fed in meal form; (4) treatment 3 fed in pellet form; (5) complete mixed diet reground through a hammer mill (541 µ) fed in meal form; and (6) treatment 5 in pellet form. Overall (d 0 to 21), ADG and ADFI decreased when corn was finely ground and fed in meal form but increased when fed in pelleted form, resulting in a tendency (P < 0.09) for a diet form × corn particle size interaction. Fine-grinding the complete mixed diet had no effects. Pelleting diets improved (P < 0.04) ADG, F/G, ME and NE energetic efficiencies, and final BW. In conclusion, pelleting diets significantly improved performance, and reducing the particle size of corn from 737 to 324 µ improved nursery pig performance when fed in pelleted form.
Keywords: Nursery pig; Fine-grinding; Pelleting